Negotiating Effective Piano Pedagogy and Music Examinations in Penang, Malaysia. The Impact of The Associated Board of The Royals Schools of Music on Piano Instruction - Jason Tye Kong-Chiang (Wacana Seni Journal of Arts Discourse, 2005)
The notion of music as a universal element of human culture is validated by the fact that each society possesses its own unique musical system and expression. However, within this general commonality, there exist panoplies of musical and pedagogical practices. lnterestingly, in many cultures, the study of music is primarily characterized by social-cultural raisons d'etre that very often diverge from its intrinsic educational objectives and aesthetic significance. In the Malaysian context, the act of teaching and learning the piano is very much motivated by undertaking a uniquely British tradition of music examinations. A dominant force that bas been playing a key role in shaping tbe course of Malaysia's music education in the past fifty years is The Associated Board of the Royal Schools of Music (ABRSM), the country's leading foreign provider of music assessment. ABRSM, together with other imported music examination boards have played a vital role in the propagation of music examinations in Malaysia. These music assessments have become the sole benchmark for formal musical achievement in this country. Hence, it is commonly construed that the primary objective of this private music education industry is centered on meeting the syllabus requirements as prescribed by these foreign music examination boards. Consequently, these examinations have by far become an unprecedented indicator or success in the process of music learning and teaching. This curious form of modus operandi in the private music education milieu has perpetuated an examination-oriented culture that views music lessons as synonymous to music testing.